Psychoeducational Challenges in the 21st Century - VÎȘCU, Loredana-Ileana; CĂDARIU, Ioana-Eva; RAD, Dana; WATKINS JR., Clifton Edward (2025)
The volume “Psychoeducational Challenges in the 21st Century” includes two sections with papers andresearch studies by university teachers, pre-university teachers and master students. The first section, mainlytheoretical, deals with topics of interest in various fields: education (curriculum, family education culture,online education, alpha generation and technology, approach to violence in education), artificial intelligence,organizations, including military organizations, trauma, human trafficking. Each paper reflects the authors’interest in the topic , as a consequence of the effects and influences of the topic in the social, relational andorganizational fields.